Evaluation of the potential of Lotus root (Nelumbo nucifera) flour as a fat mimetic in biscuits with improved functional and nutritional properties. Issue 1 (1st January 2020) - Saeed, Syed Muhammad Ghufran; Tayyaba, Sidra; Ali, Syed Arsalan; Tayyab, Sania; Sayeed, Syed Asad; Ali, Rashida; Mobin, Lubna; Naz, Shahina
ABSTRACT: In the present study, an effort was made to incorporate lotus ( Nelumbo nucifera ) as a fat mimetic for the development of functional biscuits. Functional properties, dough rheology, pasting profile, the microstructure of dough, antioxidant activities, physical, nutritional and sensorial properties of the samples were investigated. The addition of lotus root flour (LRF) resulted in a significant increase ( P ≤ 0.05) in water absorption (57.51–72.40%) and dough stability time (7.38–13.10 min), while breakdown (802–554cP) and, setback viscosities (1154–900cP) decreased. Gluten content also decreased with the increased concentration of LRF, hence suggested weaker gluten network, which was further confirmed by scanning electron microscopic images (SEMIs) of biscuits dough. The total phenolic content (17.73–131.37 mg/mL and 14.43–94.67 mg/mL), DPPH radical scavenging activity-IC50 (477.10 − 153.32 mg/mL and 500.41–94.32 mg/mL), and ferric reducing antioxidant power-IC50 (348.21–53.62 mg/mL and 350.31–36.32 mg/mL) increased upon increasing the content of LRF in wheat flour and biscuits samples. Nutritional data revealed that protein (11.20–13.40%), ash (0.53–2.86%), and the crude fiber content (0.21–15.60%) of biscuits increased, and calories reduced (497–375kcal/100 gm). Therefore, this study explores the potential of using LRF as a fat mimetic in biscuits with the application on a commercial scale to enhance antioxidant, physical, nutritional, and sensory attributes.